Pervasive Monitoring and Opportunistic Security: Defending the Internet's Protocols - Leiba, Barry (IEEE internet computing, 2015)
How can standards working groups protect Internet users from pervasive monitoring, where users' data are being massively collected, aggregated, and analyzed?